Utility of initial induction chemotherapy with 5-fluorouracil, cisplatin, and docetaxel (DCF) for T4 esophageal cancer: a propensity score-matched analysis. Issue 4 (28th November 2017) - Makino, T; Yamasaki, M; Miyazaki, Y; Wada, N; Takahashi, T; Kurokawa, Y; Nakajima, K; Takiguchi, S; Mori, M; Doki, Y
SUMMARY: Although no consensus is available on the treatment of esophageal squamous cell carcinoma (ESCC) invading adjacent organs (T4), establishing effective induction treatments is crucial to altering an unresectable status and achieving curative resection. Here, we evaluated the efficacy of chemotherapy using 5-fluorouracil, cisplatin, and docetaxel (DCF) as the initial induction treatment for T4 ESCC. Fifty patients without distant metastasis who underwent initial induction chemotherapy using DCF for T4 ESCC were propensity score-matched with 50 patients who underwent radiotherapy concurrent with cisplatin and 5-fluorouracil (CRT). In the DCF group, 24 (48.0%) patients underwent surgery, achieving a 64% clinical response rate compared to 72.0% for induction CRT. CRT was also performed in another 24 (48.0%) patients in the DCF group in whom surgical resection was not indicated. The DCF group had significantly higher overall resectability than the CRT group (78.0% vs. 48.0%, P  = 0.0017). The esophageal perforation rate during induction treatments was significantly lower in the DCF group than the CRT group (4.0% vs. 18.0%, P  = 0.0205). Prognosis was significantly better in the DCF group than the CRT group (5-year cancer-specific survival 42.1% vs. 22.2%, P  = 0.0146). Thus, induction DCF chemotherapy in patients with T4 ESCC reduced esophageal perforation and increased overall resectability, leading to better survival than CRT alone. Therefore, DCF chemotherapy may be an effective and safe option for initial induction treatment of T4 ESCC.